Pemanfaatan Data Analytics Berbasis Teknologi Dalam Bisnis Ritel Es Teh Segar - Muh. Fawaidul Makkiyah; Rahmat Shofan Razaqi; Nur Azizah (LKP KARYA PRIMA KURSUS, 2026)
The application of data analytics in technology-based retail business has become a key factor in improving the efficiency and effectiveness of business processes by analyzing data collected from various sources. This study aims to analyze how the utilization of data analytics technology is applied in the business processes of Es Teh Segar Mantap retail and to measure the extent to which the use of data analytics can improve the efficiency and effectiveness of business processes at Es Teh Segar Mantap retail. This research approach is quantitative. This approach is very strong because it prioritizes the collection of data in numerical form using statistical analysis. This study was conducted deliberately (Purposive Sampling) in Suren Hamlet, Tepos Village, Banyuglugur District, Situbondo Regency. In this study random sampling was used. The results of this study show that the integrated use of data analytics has a tangible impact on the business performance of Es Teh Segar Mantap. Based on the results of sales analysis in the Es Teh Segar Mantap business, the original flavor variant contributed the most to sales, reaching more than 83% of total sales